Income Increase of Farmers Through Utilization of Acacia Logging Residues For Wood Chips - Wildayana, Elisa (HABITAT, 2016)
The research aimed to examine feasibility of acacia logging residues and to increase farmers' income through utilization of acacia logging residues for wood chips. The research was conducted in District of Ogan Komering Ilir (OKI), South Sumatra. This research was a case study and the analysis unit is chips mills development at Village Unit Cooperatives.Â  Data was collected through questionnaires, in-depth interview, observation and desk study. The research resulted that Scenario 1 is the best priority in terms of its effectiveness in reducing operating costs followed by Scenario 2 and Scenario 3 because Scenario 1 can produce maximum income compared to other Scenarios. Financial feasibility of present conditions is compared to Scenario 2 because chips mills in Scenario 2 utilized also 100 % acacia logs. Present condition means that acacia logs are transported directly to HTI Company of chips mills and fully managed by the HTI Company. This comparison shows that Scenario 2 is less profitable compared with those on the present condition. To gain high income, it is recommended if Scenario 1 is applied which utilize 100 % of acacia logging residues for making chips mills with B/C 35.47, NPV Rp 80,674.50 Mills, IRR 670.29 % and BEP at 4,704.65 tons/year. Another alternative can be applied for Scenario 3 by using raw materials with a combination of acacia logs (50 %) and acacia logging residues (50 %) with B/C 20.45; NPV Rp 45,418.52 Mills and IRR 394.70 % with BEP at 7,989.52 tons/year.